Surface electron accumulation and enhanced hydrogen evolution reaction in MoSe2 basal planes. (June 2021) - Chang, Y.S.; Chen, C.Y.; Ho, C.J.; Cheng, C.M.; Chen, H.R.; Fu, T.Y.; Huang, Y.T.; Ke, S.W.; Du, H.Y.; Lee, K.Y.; Chao, L.C.; Chen, L.C.; et al.
Abstract: The spontaneous formation of surface electron accumulation (SEA) was observed in synthesized molybdenum diselenide (MoSe2 ) layered crystals with two-hexagonal (2 H) structure. An anomalously high electron concentration at the surface up to 10 19 cm −3 is several orders of magnitude higher than that (3.6 × 10 12 cm −3 ) of the inner bulk. The SEA is found to be generated easily by mechanical exfoliation and room temperature deselenization. Se-vacancies have been confirmed to be the major source resulting in SEA and n-type conductivity, and also the active sites for electrochemical catalysis in MoSe2 . Noted that the SEA conjugated with the Se-vacancy-related surface defects enhances the electrochemical hydrogen evolution reaction (HER) activity substantially. The optimized HER efficiency with an overpotential at 0.17 V and Tafel slope at 60 mV/dec of the basal plane of 2 H-MoSe2 was achieved by the nitrogen plasma treatment, which has outperformed several nanostructures, thin films, and hybrid counterparts. This study reveals the intriguing surface-dominant electronic property and its effect on the HER enhancement of the basal plane, which is crucial for development of a stable, low-cost and highly efficient catalyst using 2 H-MoSe2 . Graphical Abstract: ga1 Highlights: Anomalous surface electron accumulation (SEA) was discovered in synthesized MoSe2 . Se-vacancies caused by spontaneous deselenization have been confirmed to be the origin of the SEA and n-type conductivity in MoSe2 . The SEA conjugated with surface defects substantially enhances the electrochemical hydrogen evolution reaction (HER) activity. The HER efficiency of nitrogen plasma-treated 2H-MoSe2 outperforms several nanostructure and hybrid counterparts.